ANALISIS BASE SHEAR STRUKTUR YANG MENGALAMI KERUSAKAN DENGAN CARA THA, CQC DAN SRSS AKIBAT BEBAN GEMPA - Musbar Musbar (Politeknik Negeri Lhokseumawe, 2011)
This study aims to analysis of base shear structure from effects of earth quakes. The methods were used to analysis with damage scenarios as follows: THA, CQC, and SRSS. The damage scenarios simulation was obtained by applying reduced stiffness on a bottom column element of frame. The reduced stiffness of column elements with damage scenarios as follows: 0%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, and 40%. CAL-91 was used for analysis and for obtaining base shear and frequency of structure. More big damage scenarios to apply at element bottom column of frame that reducing value of frequency and base shear of structure. The method THA only stable until damage scenarios 25%, while method CQC and SRSS stable permanent up to damage scenarios 40%.Key words: base shear, damage scenarios, THA, CQC, SRSS